Development of analytical approach to evaluate (diffServ-MIPv6) scheme - Hussien, Loay F.; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Khalifa, Othman Omran; Hameed, Shihab A. (Maxwell Scientific Organization, 2012, 2014)
: The aspiration of Mobile IPv6 is to provide uninterrupted network connectivity while the mobile node is moving between different access points or domains. Nonetheless, it does not provide QoS guaranteed to its users same as the traditional Internet protocol IP. It merely can provide Best-Effort (BE) service to all its applications despite of the application requirements. The future wireless network would be based on IPv6 to provide services to Internet mobile users. Hence, one of main requirements of next generation IP based networks is providing QoS for real-time traffic that will be transporting through MIPv6 networks. This study presents the analytical analysis for the previously proposed scheme (DiffServ-MIPv6) that applies the DiffServ platform to Mobile IPv6 network in order to suit the needs of both QoS guaranteed and mobility in communication. The analytical evaluation is developed to assess the performance of the proposed scheme (DiffServ-MIPv6) compared to the standard MIPv6 protocol in terms of signaling cost. The signaling cost is measured against two factors session-to-mobility ratio and packet arrival rate.